Das Marketing-House-Konzept - ein Denkmodell zum integrierten Verständnis des Marketing-Konzepts - Christian Lucas (IUBH Internationale Hochschule, 2020)
– Marketing has to be completely rethought in the age of the digital revolution. An expansion of existing concepts and models, as has always been done since the 1950s, is no longer sufficient here. This means that findings from the past few decades, such as consumer focus and segmentation, can be better adapted to the model. The new concept now puts the individual consumer at the center of attention and consistently aligns marketing with it. From the point of view of the consumer, it is no longer important to optimize the marketing mix, but the perceived customer-specific offer. This change of perspective has far-reaching consequences: innovation management is detached from the marketing mix, information gathering is given a more central role, and options for individualization and customer relationships are also taken better into account. The marketing instruments are no longer viewed in isolation, but always in collaboration and in interaction with the consumer. The associated increase in complexity leads, in a first step, from a personnel-centered marketing- and target group analysis to a process-oriented analysis.
Keywords: M31; 650; Marketing House; Digital Revolution; Consumer Orientation; Automated Customer Segmentation; Thought Model